Editorial - International Journal of Sustainable Energy Planning and Management Vol 28 - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2020)
This editorial introduces the 28th volume of the International Journal of Sustainable Energy Planning and Management probing into the actors engaged in energy renovation, rural district heating, and hydropower in Sulawesi. Other work address power-to-gas technology, pine needles as a source of biomass in Himalaya and finally how adaptive pricing can impact electricity demand and thus energy system performance.